2018
DOI: 10.1007/s10096-018-3322-7
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiome as a risk factor for urinary tract infections in children

Abstract: As urinary tract infection (UTI) pathogens originate from the gut, we hypothesized that the gut environment reflected by intestinal microbiome influences the risk of UTI. Our prospective case-control study compared the intestinal microbiomes of 37 children with a febrile UTI with those of 69 healthy children. We sequenced the regions of the bacterial 16S rRNA gene and used the LefSe algorithm to calculate the size of the linear discriminant analysis (LDA) effect. We measured fecal lactoferrin and iron concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 39 publications
1
40
0
1
Order By: Relevance
“…Literature investigating the role of uropathogenic genes like FimH in increasing the propensity for gut E. coli strains to cause UTI is also relatively limited 24 . Recent studies have found increased gut abundance of Escherichia or Enterococcus in patients with UTI compared to patients without UTIs 10,11 , but they did not evaluate temporal dynamics of the gut microbiota. Our study expands upon this idea by demonstrating that increased fecal abundance of Escherichia and Enterococcus is associated with an increased risk of developing future bacteriuria with the respective organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature investigating the role of uropathogenic genes like FimH in increasing the propensity for gut E. coli strains to cause UTI is also relatively limited 24 . Recent studies have found increased gut abundance of Escherichia or Enterococcus in patients with UTI compared to patients without UTIs 10,11 , but they did not evaluate temporal dynamics of the gut microbiota. Our study expands upon this idea by demonstrating that increased fecal abundance of Escherichia and Enterococcus is associated with an increased risk of developing future bacteriuria with the respective organism.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study of 26 kidney transplant recipients in which we performed serial gut microbiota profiling, we reported an association between gut Enterococcus abundance and Enterococcus UTIs 10 . In another recent case-control study of children with UTIs and without UTIs, the relative gut abundance of Escherichia coli was significantly higher in children with UTIs than children without UTIs 11 . Both of these studies assessed whether the gut microbiota is associated with UTIs at the time of UTI, but not whether the gut microbiota is a risk factor for development of bacteriuria and UTI.…”
Section: Introductionmentioning
confidence: 86%
“…The F519 primer contained an Ion Torrent pyrosequencing adapter sequence A (Lifescience Technologies, USA), a 9-bp unique barcode sequence, and one nucleotide linker, while the R926 primer contained an Ion Torrent adapter trP1 sequence. We have earlier used similar methodology for NGS and bioinformatics of fecal samples obtained in infancy 40 .…”
Section: Methodsmentioning
confidence: 99%
“…As a matter of fact, gut microbiota contributing to the diversity of prokaryotes inhabiting the urinary tract was suggested by a recent study highlighting the reduction in the recurrence of UTIs following fecal microbiota transplantation (FMT) (Staley et al, 2017;Tariq et al, 2017). It has also been recently suggested that the composition of the intestinal microbiota could impact the occurrence of UTI in children (Paalanne et al, 2018). These data suggest that UTI are in fact the consequences of ecosystem disruptions and that uropathogens could be acquired from the environment, particularly from animals (Jakobsen et al, 2010;Giufre et al, 2012;Maluta et al, 2014;Mellata et al, 2018).…”
Section: Figure 3 | Venn Diagrammentioning
confidence: 99%